2012
DOI: 10.1100/2012/895765
|View full text |Cite
|
Sign up to set email alerts
|

A Review for Solitary Plasmacytoma of Bone and Extramedullary Plasmacytoma

Abstract: Solitary plasmacytoma (SP) is characterized by a mass of neoplastic monoclonal plasma cells in either bone (SBP) or soft tissue without evidence of systemic disease attributing to myeloma. Biopsy confirmation of a monoclonal plasma cell infiltration from a single site is required for diagnosis. The common presentation of SBP is in the axial skeleton, whereas the extramedullary plasmacytoma (EMP) is usually seen in the head and neck. The ratio of SP seen at males to females is 2 : 1 and the median age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
247
2
31

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(286 citation statements)
references
References 54 publications
(143 reference statements)
6
247
2
31
Order By: Relevance
“…11 EMP has a better prognosis than other lymphoproliferative diseases, with a 10-year overall survival rate of 70%; when surgical treatment is performed along with RT, the reported median overall survival is 7-9 years. 5,12 Close follow up of patients with EMP is important because 10-20% of patients progress to multiple myeloma. 7 Our first patient underwent surgical resection and has been followed-up for three years without recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…11 EMP has a better prognosis than other lymphoproliferative diseases, with a 10-year overall survival rate of 70%; when surgical treatment is performed along with RT, the reported median overall survival is 7-9 years. 5,12 Close follow up of patients with EMP is important because 10-20% of patients progress to multiple myeloma. 7 Our first patient underwent surgical resection and has been followed-up for three years without recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of development into MM is increased within 2 years following diagnosis, it has been demonstrated to occur even after 15 years of disease free period [1,3,22], suggesting the need for a long-term follow-up. Although some authors consider that plasmacytoma converted into MM has better prognosis than classic MM [23] our patient died from the disease after 4 months despite intensive treatment. So far no tumor related factors that can predict the progression towards MM have been identified, nor hasn't prophylactic chemotherapy proven to be effective [19,21,23].…”
Section: Discussionmentioning
confidence: 56%
“…In a recent review on EMPs, Kilciksiz et al [23] reported 5-and 10-year overall survival rates of 71 and 69 %, and a 10-year local control rate between 73 and 100 %. Subsequent to endoscopic excision followed by a 40 Gy irradiation regimen (in accordance with current recommendations), we achieved a 5-year OS of 65 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMP is a rare plasma cell tumor. The majority (80 %) of the EMPs occur in the head and neck, especially in the nasopharynx and paranasal sinuses [1]. On initial presentation, these tumors must be differentiated from multiple myeloma (MM).…”
mentioning
confidence: 99%